Sociocultural integration of meskhetian turks in the context of inter-ethnic cooperation - Afanasieva, L.; Bukrieieva, I.; Glyns' ka, L.; Hlebova, N.; Oleksenko, Roman; Олексенко, Роман Іванович; Олексенко, Роман Иванович (My University, 2021)
EN: The article considers the main stages of formation, the main internal and external factors of development of the Ukrainian community of Meskhetian Turks in the current contexts of socio-political realities of today. Based on the analysis of theoretical sources and applied research of problems, factors, nature and directions of ethnocultural adaptation of Meskhetian Turks in Ukraine, there are the tendencies of growth of social mobility and migration activity, democratization of marital and family relations, diversification of employment, significant changes in social, cultural and educational environment, places of compact residence of Ukrainian Meskhetian Turks. The culturological and sociological study of the problems of sociocultural adaptation and the definition of the content elements and the target direction of the system target regional programs of ethnocultural adaptation of the youth of Meskhetian Turks in Ukraine are actualized. It is justified the need to predict sociocultural trends and timely creation of adequate mechanisms and development the forms and methods of coordination of cultural policy in the field of education in the multicultural environment of the south-eastern regions of Ukraine. UK: В статті розглянуті основні етапи становлення, основні внутрішні і зовнішні чинники розвитку української громади турків-месхетинців в актуальних контекстах соціально-політичних реалій сьогодення. На основі аналізу теоретичних джерел і прикладних досліджень проблем, чинників, характеру і спрямувань етнокультурної адаптації турків-месхетинців в Україні засвідчують тенденції зростання соціальної мобільності і міграційної активності, демократизації шлюбно-сімейних відносин, диверсифікації форм зайнятості, значних видозмін в соціальному, культурному та освітньому середовищах місць компактного проживання українських турків-месхетинців. Актуалізується культурологічне і соціологічне вивчення проблем соціокультурної адаптації та визначення змістових елементів і цільового спрямування системних цільових регіональних програм етнокультурної адаптації молоді турків-месхетинців в Україні. Обґрунтовується потреба прогнозування соціокультурних тенденцій і своєчасного створення адекватних механізмів і розробки форм і методів координації культурної політики в сфері освіти у полікультурному середовищі південно-східних регіонів України.
Соціокультурна інтеграція турків-месхетинців в контексті міжетнічного співробітництва
Keywords: Turkish-Meskhetian community of Ukraine; sociocultural adaptation; multicultural territorial community; principle of interculturality; ethnocultural policy; турецько-месхетинська спільнота України; соціокультурна адаптація; багатокультурна територіальна громада; принцип інтеркультурності; етнокультурна політика